Does Information and Communication Technologies Sustain Economic Growth? The Underdeveloped and Developing Countries Case - Erkan Erdil; Burcu Türkcan; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2009)
This paper tests the impact of ICT on economic growth for underdeveloped and developing countries by using a panel dataset for the period of 1995-2006. We first develop the theory between ICT and economic growth. We show that ICT-capital has a positive effect both on long-run and transitional income per capita, if it is considered as a factor of production. Next, we estimate a panel data set with 131 underdeveloped and developing countries under the assumption that ICT is one of the determining factors of economic growth. We find that ICT has positive and significant effect on economic growth even after the use of some control variables.
Keywords: C33; O5; O33; 330; ICT; economic growth; Panel Data; GMM; human capital; developing countries; underdeveloped countries; Wirtschaftswachstum; Informationstechnik; Entwicklungsländer